Perbandingan Akurasi Kwh Meter Digital Dan Kwh Meter Analog - Zuhri, Muhammad Ridho Rohman, Ir. Jatmiko, M.T (2017)
Electrical energy cannot be separated from daily human needs. In modern times, we are all dependent on electricity for our communication, transportation, and more. It is especially important at home where we use it to help wash our clothes, power fans to cool us down, or give us light at night. Electrical energy used in housing is automatically calculated by PT. PLNusing a measuring instrument, like a kWh meter for example. There are two types of kWH meters that PT.PLN uses: the kWh analogue meter and the kWh digital meter. This study aims to determine the accuracy of the kWh meter. This will be done by installing a series of two postpaid electricity meters with a prepaid meter. Data will be obtained through the addition of kWh on the postpaid electricity meter and the reduction of kWh on the prepaid electricity meter by using a resistive load. From the results of this study, it can be concluded that the average percentage of error readings for resistive loads (cos φ=1) amounted to 11.498% contained in the digital meter kWh. On testing in the second home, the digital kWh meter had 5 times as many erroneous readings over 30%. In comparison, the analogue kWh meter on had 1 kWh reading of 8.043% and 2 kWh reading of 8.369%. To develop this research, we can use capacitive or inductive loads.